Software Ageing Prevention from Software Maintenance Perspective – A Review - Abdullah, Zuriani Hayati; Yahaya, Jamaiah H.; Mansor, Zulkefli; Deraman, Aziz (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
This paper presents the background study of software ageing phenomenon and the prevention techniques to contravene the ageing. The accumulation of software failure and degradation of software performance shows that the software gets old and irrelevant to the users in the environment. Ageing of the software might contribute to the negative impact and affect organisational performance. It is crucial for the organisation to find out prevention actions toward the software ageing phenomenon. This paper discussed in detail how software maintenance activity can be used as ageing prevention for software ageing.